Crystal structure of RlmA(I): Implications for understanding the 23S rRNA G745/G748-methylation at the macrolide antibiotic-binding site - Das, Kalyan (National Academy of Sciences, 2004)
The RlmA class of enzymes (RlmA(I) and RlmA(II)) catalyzes N1-methylation of a guanine base (G745 in Gram-negative and G748 in Gram-positive bacteria) of hairpin 35 of 23S rRNA. We have determined the crystal structure of Escherichia coli RlmA(I) at 2.8-Å resolution, providing 3D structure information for the RlmA class of RNA methyltransferases. The dimeric protein structure exhibits features that provide new insights into its molecular function. Each RlmA(I) molecule has a Zn-binding domain, responsible for specific recognition and binding of its rRNA substrate, and a methyltransferase domain. The asymmetric RlmA(I) dimer observed in the crystal structure has a well defined W-shaped RNA-binding cleft. Two S-adenosyl-l-methionine substrate molecules are located at the two valleys of the W-shaped RNA-binding cleft. The unique shape of the RNA-binding cleft, different from that of known RNA-binding proteins, is highly specific and structurally complements the 3D structure of hairpin 35 of bacterial 23S rRNA. Apart from the hairpin 35, parts of hairpins 33 and 34 also interact with the RlmA(I) dimer.